Assistance for Arrangement of Financial Reporting "Batik Ismoyo" - Sholihin, Muhammad Rijalus (Empowerment Society, 2020)
Every effort made by the community should get assistance for the activities they carry out, especially in business development they are undertaking, including the problem of preparing financial reports, small and medium enterprises such as Batik Ismoyo are also still in most other umkm companies, namely the need for guidance to be able to compile reports good and true finance. Based on the results of the partner situation analysis above, it can be concluded that Batik Ismoyo, whose address is in need of guidance in terms of MSME development in terms of simple financial reporting. The method we do is to provide assistance in the preparation of financial reports, starting from providing knowledge about the importance of financial reports, providing assistance in preparing financial reports in accordance with the business owned, with a simple recording method regarding accounting treatment to discuss financial problems that exist in Batik Ismoyo. The result of this assistance is that Batik Ismoyo has been able to compile financial reports well, including reading the results of the report.